2011
DOI: 10.1016/j.actbio.2010.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Fetal bovine serum xenoproteins modulate human monocyte adhesion and protein release on biomaterials in vitro

Abstract: Monocyte-derived macrophages are critical in the host foreign body response to biomaterials and have been studied extensively in various culture conditions in vitro such as medium supplemented with fetal bovine serum (FBS) or autologous human serum (AHS). Since monocyte maturation into macrophages is highly plastic and may vary considerably depending on the surface, isolation procedures, and in vitro culture conditions, we hypothesize that variations in protein adsorption and serum type will greatly impact mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
(56 reference statements)
5
8
0
Order By: Relevance
“…Several groups already demonstrated that differences in serum concentration or type could highly affect cell adhesion (Fujiwara et al, 2009;Grinnell and Feld, 1979;Schmidt et al, 2011). Our study confi rmed that serum greatly affects cell adhesion in addition to surface patterning.…”
Section: Wwwecmjournalorg E Lamers Et Al Dynamic Cell Adhesion Andsupporting
confidence: 59%
“…Several groups already demonstrated that differences in serum concentration or type could highly affect cell adhesion (Fujiwara et al, 2009;Grinnell and Feld, 1979;Schmidt et al, 2011). Our study confi rmed that serum greatly affects cell adhesion in addition to surface patterning.…”
Section: Wwwecmjournalorg E Lamers Et Al Dynamic Cell Adhesion Andsupporting
confidence: 59%
“…The serum was added in a minimum dose for stimulation of cell adhesion to plastic [30]. In the monolayer passage 1 RPE culture, 90-95% cells had epithelial phenotype (Fig.…”
Section: Cultures Of Passage 1 and Passage 3 Rpe Cells Grownmentioning
confidence: 99%
“…For example, differences were observed in adherent density and cytokine release profiles of primary human monocytes exposed to TCPS and poly(ethylene glycol) (PEG) hydrogel surfaces cultured in either fetal bovine serum (FBS) or autologous human serum (AHS) [12]. The effect of serum source was most evident in the observed 3- and 10-fold increase in adherent cell density on TCPS and PEG hydrogel surfaces, respectively, when AHS versus FBS was employed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this decrease in adherent density is usually accompanied by a temporal alteration in cell behavior ( e.g. cytokine or growth factor release) [11, 12, 2124]. The mechanism regulating the decrease in monocyte adherent density on these substrates and its possible impact on cell behavior, however, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation